McGraw-Hill's financial analyst (New York : McGraw-Hill, 1995)
Presents 16 articles on the history of oceanography, marine ecosystems, and marine biodiversity. Includes interviews with 8 world-renowned scientists, 450 photos, 175 marine fact sheets, 100 species profiles, 3D animations, 45 min. of videos, and internet links for further study.
3.5 in disc (312)
System requirements : IBM PC 80386 or higher, Microsoft Windows 3.1 or higher, 4 Mb RAM, 12 Mb hard disk space.
Keywords: Business enterprises -- Finance -- Computer software; Corporations -- Finance -- Computer software; Οπτικοακουστικό υλικό.